THE INFLUENCE OF PRICE AND PROMOTION MODERATED BY SERVICE QUALITY ON PURCHASE INTENTION IN PT MAYBANK INDONESIA FINANCE - Ricky Hertanu; Soegeng Wahyoedi; Saparso Saparso (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
This study discuss about moderated role of price and promotion service quality to purchase intention at PT Maybank Indonesia Finance. The sampling procedure used in this research is non-probability with purposive sampling technique . Researcher spread questionnaire to 95 respondents. Data analysis using Smart PLS analysis. Analysis result conclude that, price have positive and significant influence on purchase intention. So could say, price good will influence purchase intention at Maybank Finance. Promotion has influence negative and no significant to purchase intention . So could it is said, the promotions carried out by the company are not take effect to purchase intention at Maybank Finance. Service quality no moderate price to purchase intention. So could said, service quality no give effect booster or weakening from variable price that. Service quality moderate promotion to purchase intention. So could said, service quality give effect booster to variable promotion.